The use of Industrial Posters and Graphic Expressions in acquiring the concepts of the Prophet's biography for Students of Qur’anic Science and Islamic Education - Mohammed , Yousif; Tawfeeq, Marwan (Islamic Sciences Journal, 2023)
The world is witnessing tremendous development and progress in all areas of life, including the field of education and the means used in it. Therefore, the researchers sought to identify the use of (industrial) murals and graphic expression and their impact on acquiring the concepts of the Prophet’s biography among students of the Department of Quranic Sciences and developing their altruistic behavior to learn from the material. The researchers designed a partial controlled experimental design and intentionally selected a sample of second-year students in the Department of Qur’anic Sciences at the College of Education for Human Sciences, Tikrit University, and on the classroom platform for e-learning. The sample consisted of (77) students who were divided into three classes, and by (27) students for the first experimental group, (25) students for the second experimental group, and (25) students for the third control group. The researchers rewarded the research groups as mentioned in the limits of the research. The research subject (the Noble Biography of the Prophet for the second stage in the departments of Quranic sciences and Islamic education), and in the light of its content, the researchers identified the Islamic concepts from the Biography of the Prophet, which numbered (14) concepts, and in light of it, the researchers prepared behavioral goals numbering (60) behavioral goals, and prepared plans Teaching, the researchers prepared a test for acquiring the concepts of the Prophet's biography of the type (multiple choice) of (30) paragraphs. The two researchers verified the apparent validity, the content validity, its discriminatory strength and the difficulty coefficient, and extracted its stability using the Pearson correlation coefficient, which amounted to (0.84). The two researchers adopted the Altruistic Behavior Scale of Al-Daoudi (2004), the researchers studied the two research groups themselves, and after completing the experiment, the researchers applied the test of acquiring concepts in the Prophet’s biography and the dimensional altruistic behavior scale on the research groups, and after completing the application, the data were statistically treated using the SPSS computer program. The fourth chapter includes the conclusion and in the fifth chapter, the researchers concluded, recommended and make the suggestions.